The Role of Short Videos on Social Media in Increasing Interest in Learning Arabic Among Generation Z: Opportunities and Challenges - Siti Rifatul Milah; Siti Zahrotul Azizah; Raudina Rihhadatul ‘Aisy (Kitaba, 2025)
The integration of social media into Arabic language learning has become a significant trend in the digital era, particularly among Generation Z, who have grown up as digital natives. This article examines the role of short-form videos on social media platforms—specifically TikTok, Instagram, and YouTube—in enhancing students’ interest in learning Arabic, while identifying the accompanying pedagogical opportunities and challenges. The study employs a Systematic Literature Review (SLR) method based on the PRISMA framework, analyzing 18 scientific studies published between 2019 and 2024 sourced from Google Scholar, ERIC, and DOAJ databases. Data were analyzed thematically to identify patterns of effectiveness, student engagement, and pedagogical implications. The findings indicate that short-form videos on social media significantly increase learning interest through visually engaging, interactive, and contextual content delivery. TikTok excels in fostering creative engagement and active participation, YouTube supports self-directed learning and flexible access, while Instagram proves effective in vocabulary acquisition through visual representation. However, implementation faces serious challenges, including distractions from entertainment content, inconsistent quality of educational materials, privacy risks, and the emergence of a "digital empathy gap." Furthermore, the limited availability of content that promotes spiritual and character development remains a significant drawback. This article provides a comprehensive conceptual map and concrete pedagogical recommendations for educators, researchers, and developers of digital learning media. The findings affirm that social media is not merely a cognitive tool, but also holds potential for socio-spiritual transformation when used strategically.